Jonathan Dawson and Some Early Nineteenth Century Baptist Networks in London. (2nd October 2018) - Copson, Stephen
ABSTRACT: This piece seeks to illustrate that in London in the first quarter of the nineteenth century there existed significant Baptist networks that brought together ministers and lay people with common interests in church, philanthropy and education that both embraced and went beyond solely denominational concerns.